Isn’t it time we transitioned to integrated sustainability? De-codifying the hard-soft divide from a systems-theoretic perspective - Chaker, Fadwa; Bonsu, Samuel K; El Ghaib, Majid K; Vazquez-Brust, Diego (Sustainability accounting, management and policy journal (Print), 2021)
Purpose The instrumental-normative divide that has historically characterized approaches to societal sustainability has also resulted in a rift between underlying mental models and methods destined to address the issue. This separation makes our understanding and tackling of the present global ecological problems only limited and ineffective. The present work aims to draw on theoretical background to develop a conceptual framework for transitioning to integrated corporate sustainability. Design/methodology/approach Drawing inspiration from Luhmann’s (1995) theory of social systems, we consider the instrumental (hard) and normative (soft) methods (Jackson 2019) for corporate sustainability as “conceptual systems” that derive much of traditional social systems’ attributes. These systems are autopoietic, complexity-reducing and functionally differentiated. Following Luhmann’s philosophical grounding, we suggest that integrating the two systems of hard and soft methods boils down to constraining both systems’ internal complexity by imposing limitations on their operational structures. This translates into a decodification–recodification process whereby new methods emerge as a combination of initially disconnected structures. Findings The proposed conceptual integration framework is applied to the case of the Sustainability Balanced Scorecard (SBSC) which has been recently subject to inconclusive controversy. Our work demonstrates that redesigning the SBSC’s architecture following the presented framework leads to embracing complexity, tensions and conflict all the while offering a systematic approach for properly identifying and quantifying cause–effect relationships. Moreover, the proposed framework scores high in Complexity and Systemicity measures, making it both durable and practically useful. More generally, this work drives home the point that an integrated approach to sustainability management is not only important but also feasible and theoretically durable. Research limitations/implications Theoretically, the present work underscores the contribution of systems theory, and particularly the Luhmannian perspective, to transcending some of the most salient “divides” in approaches to societal sustainability. The decodification–recodification process not only enables integrating two distinct conceptual systems, but it also transforms the divide into an opportunity to gain a fresher perspective on one of the most challenging issues of our time. This process may demand, however, some adjustments as we move across various function systems, which requires solid knowledge and understanding of the underlying “codes” that define the systems subject to integration. Practical implications This work implies that integration of varied and sometimes outwardly opposed function systems can and must be carried out to achieve larger societal impact. With respect to the illustrated case, the emerging dynamic SBSC offers a viable strategic planning platform whereby managers and stakeholders can concurrently define, forecast and adjust the societal strategy that maximizes triple bottom-line indicators and sustainable development impact. Social implications Providing decision and policymakers with integrated sustainability management approaches and instruments will have a direct benefit on enhancing the way systems, and large corporations in particular, treat and deal with nature and human beings. Originality/value We propose that proper integration of multiple function systems, employing integrative, unbiased and structured methodologies, can be decisive in challenging current practices in sustainability management and in providing informed guidance for making the high-stake decisions needed in the transition towards sustainable development of business and society.